Pos-pandemic era inquiry tendency for substances prohibited in sports: Data analysis of Taiwanese anti-doping services - Chen, C. C.; Lin, T. Y.; Chen, C. H.; Wang, C. Y.; Wu, Y. T.; Hsu, M. C.; Chang, W. C. W. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: World Anti-Doping Agency (WADA) updates its prohibited list(1) annually according to the latest research and reports, making it difficult for sports and medical professionals to keep track of all the latest information and memorized which healthcare products contain substances prohibited in sports. To assist Taiwanese athletes and people concerned, anti-doping authorities in Taiwan provide services utilizing website search tools, APP, and online professional consultation. Analysis data collected from these services allow us to identify the population in need and the types of issues or substances that athletes may encounter in daily life, improving the efficiency of sports-prohibited substance misuse prevention.